1996
DOI: 10.1016/0014-5793(95)01488-8
|View full text |Cite
|
Sign up to set email alerts
|

Post X‐ray crystallographic studies of chymosin: the existence of two structural forms and the regulation of activity by the interaction with the histidine‐proline cluster of κ‐casein

Abstract: Calf chymosin molecules exist in the two alternative structural forms: the first one has S~ and $3 binding pockets occluded by its own Tyr 77 residue (the self-inhibited form); the second has these pockets free for a substrate binding (the active form). The preliminary incubation of the enzyme with a pentapeptide corresponding to the histidine-proline cluster of the specific substrate it-casein results in a 200-fold increase of the hydrolysis rate for the enzyme 'slow substrate'. The result suggests that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 17 publications
3
26
0
Order By: Relevance
“…Structural studies of chymosin clearly indicated that specific cleavage of the bond between Phe105 and Met106 (P1-P1′) in -casein, responsible for the high level of milk-clotting activity of this enzyme, was assisted by electrostatic interactions between a positively charged cluster His-Pro-His-Pro-His at positions P8-P4 (98–102) of the casein substrate and the negatively charged residues in loop 244–248 of chymosin (a structural equivalent of loop 238–245 in HAP)2224. N-terminal extension beyond the P6 position of the peptide substrates also increased the catalytic efficiency of cathepsin E and of several members of the plasmepsin family25.…”
Section: Resultsmentioning
confidence: 99%
“…Structural studies of chymosin clearly indicated that specific cleavage of the bond between Phe105 and Met106 (P1-P1′) in -casein, responsible for the high level of milk-clotting activity of this enzyme, was assisted by electrostatic interactions between a positively charged cluster His-Pro-His-Pro-His at positions P8-P4 (98–102) of the casein substrate and the negatively charged residues in loop 244–248 of chymosin (a structural equivalent of loop 238–245 in HAP)2224. N-terminal extension beyond the P6 position of the peptide substrates also increased the catalytic efficiency of cathepsin E and of several members of the plasmepsin family25.…”
Section: Resultsmentioning
confidence: 99%
“…The role of some of these bonds has been analyzed by site-directed mutagenesis, such as Thr77Val, and lowered catalytic efficiency was observed [66]. Interactions of pepsins with large peptides or proteins may also occur at the edge or outside the cleft, and for these cases, more substrate-binding pockets such as S 8 through S 5 subsites are anticipated [67]. Some residues, such as Lys319, far from the cleft, have been shown to be involved in catalysis by sustaining the flexibility of the enzyme [68].…”
Section: Tertiary Structurementioning
confidence: 98%
“…Bovine chymosin cleaves the Phe105-Met106 bond of k-casein of bovine milk, resulting in clotting [100]. A negatively charged region near the edge of the active-site cleft, consisting of Glu244, Asp246, Asp248, and Asp250, is involved in this specific cleavage [67], and Asp246 and Asp248 are common to all chymosins except for the chicken enzyme, being replaced by non-charged residues in pepsins A and gastricsins ( fig. 2).…”
mentioning
confidence: 97%
“…13 These features are also found in other aspartic proteases showing strong homology within the protein family. 9, [14][15][16] The substrate of chymosin, κ-casein, is a 169 residue peptide found on the surface of milk serum aggregates called casein micelles. 17 Chymosin selectively cleaves the Phe105-Met106 bond in κ-casein, which destabilises the casein micelles leading to the release of insoluble casein proteins causing milk clotting.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The HPHPH cluster is conserved in many other mammalian κcasein peptides including buffalo and goat, but in camel κ-casein the three histidine residues are mutated to arginines. 1,5 Although the allosteric activation process has been widely discussed in the literature, 1,7,16,[19][20][21] the mechanism has not been elucidated at a molecular level due to the challenges associated with studying it by experimental methods. This has hindered the development of novel enzymes and enzymatic processes for the food industry.…”
Section: Introductionmentioning
confidence: 99%